Sensational senses : amazing ways animals perceive the world - Hirsch, Rebecca E. (Millbrook Press, 2022)
"Humans have five senses. But some animals can perceive things we can't thanks to their extraordinary senses. From science writer Rebecca E. Hirsch comes a fascinating book that introduces these animals and delves into the science behind their senses. Discover how animals use their senses to find food, navigate their environment, and communicate. Featured animals include the star-nosed mole with its highly developed nose, the deadly sidewinder rattlesnake which uses its pits to strike its prey, and the electric eel that uses electroreception to sense its prey." -- Amazon.com.